The Views of Contemporer Mut'ah Marriage among Yogyakarta Shi’ite Leaders - Muhammad Muhajir; Muhammad Fadli Kamil (Jurnal Dialog, 2021)
This paper explicates the views of Shia leaders in Rausyan Fikr Foundation Yogyakarta on mut'ah marriage. There have been various views related to mut'ah marriage law by Rausyan Fikr leaders. On one side, Shi’ite school of thought is hitherto the only proponent to the mut'ah marriage. This research is descriptive-analytic study using normative approaches by examining the views of Yogyakarta Shi’ite leaders in justifying the marriage using Islamic law including the Qur'an, Hadith, and Fiqh principles or ushuliyyah. The study finds that there are three opinions among Shi’ite leaders in Yogyakarta; 1) Some leaders strictly prohibit due to the differences in places and conditions between Indonesia and Iran, 2)Some of them allow it with the condition that marriage must be conducted with fellow Shi’ite, 3) Some believe it is allowed according the Ja'fari school of thought without considering conditions and places. Despite the differences of views among Yogyakarta Shia leaders, these differences can be compromised by seeing that mut'ah marriage is unacceptable under normal circumstances, but in an emergency situation, it can certainly be justifiable by considering its maslahat (benefit) or mudarat (danger). Keywords: mut'ah marriage, Islamic law, Yogyakarta Shia leaders Tulisan ini membahas tentang nikah mut’ah dan penerapannya dalam pandangan tokoh Syiah di Yayasan Rausyan Fikr Yogyakarta. Diketahui bahwa terjadi perbedaan pandangan terkait hukum nikah mut’ah oleh para tokoh Rausyan Fikr. Di sisi lain, kita ketahui bahwa mazhab Syiah adalah satu-satunya mazhab yang konsisten dengan argumentasi bahwa nikah mut’ah tetap berlaku hingga akhir zaman. Penelitian ini merupakan penelitian lapangan (field research) bersifat deskriptif-analitik dengan menggunakan pendekatan normatif dengan mengkaji pandangan para tokoh Syiah Yogyakarta menggunakan hukum Islam secara mayoritas meliputi al-Qur’an, Hadis dan kaidah-kaidah fiqhiyyah ataupun ushuliyyah. Hasil penelitian ini adalah terdapat tiga pendapat dari tokoh Syiah di Yogyakarta; yaitu 1) melarang secara mutlak dengan alasan perbedaan tempat dan kondisi antara Indonesia dan Iran, 2) membolehkan dengan syarat pernikahan harus dilakukan dengan sesama penganut Syiah, 3) membolehkan secara mutlak berlandasan pada fikih mazhab Syiah Ja’fari tanpa mempertimbangkan perbedaan kondisi dan tempat. Terlepas perbedaan pandangan di kalangan tokoh Syiah Yogyakarta, perbedaan tersebut dapat dikompromikan dengan melihat bahwa nikah mut'ah tidak dapat diterima dalam keadaan normal, namun dalam keadaan darurat tentu dapat dipertimbangkan dan dilihat mana lebih besar maslahat dan mudaratnya. Kata Kunci: nikah mut’ah, hukum Islam, tokoh Syiah Yogyakarta